Leading in disadvantaged Zimbabwean school contexts: Female school heads’ experiences of emotional labour - Zikhali, Joyce; Perumal, Juliet (Educational Management Administration and Leadership, 2016)
This qualitative multiple case study explored the sources of emotional stress experienced by 12 female Zimbabwean primary heads leading in socio-economic disadvantaged schools in Masvingo District and their attempts to alleviate the challenges that the children from these disadvantaged contexts presented them with. Data was generated through individual semi-structured interviews, and observations and the data was analysed thematically to elicit the sources of their emotional labour that emanated from stress-related cultural and contextual factors. The study revealed that despite the school heads experiencing anxiety, pain, sorrow, sympathy, frustration, sadness, and concern they were happy about their appointments to leadership positions. The sources of their emotional stress were related to the plight of children; stereotypical gender expectations; lack of parental cooperation; and unrealistic professional and social expectations. The study suggests wellness recesses; the establishment of social networks through which heads could share their experiences; and professional development programmes on stress management as possible interventions that could help the heads deal with these stressful circumstances. © 2015, © The Author(s) 2015.
Keywords: 2000 à aujourd'hui; 2010-2019; afrique; directrices d'école; enfants orphelins; environnement; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail; travail émotionnel; zimbabwe; éducation